Community education about stunting in Neglasari Village Tasikmalaya Regency - Agim Agustiar Priyadi; Ahmad Julkipli; Rasim Rasim (Universitas Pendidikan Indonesia, 2024)
Stunting is a problem of malnutrition caused by providing food that does not meet nutritional needs. It also reflects stunted growth due to poor nutrition and poor health before and after birth. Based on service in Neglasari Village, the main problem was identified: the lack of public understanding about stunting and related information. Even though the stunting rate in Neglasari Village is relatively low, it is essential to create awareness and preventive efforts. Therefore, this service aims to educate the people of Neglasari Village, Salawu District, and Tasikmalaya Regency regarding stunting. The method applied in this service is counseling for one month at every Posyandu in Neglasari Village. The service team provides education in collaboration with village officials and community health centers to conduct outreach related to stunting in Neglasari Village. Based on the results of the service implementation, it can be concluded that there is still a lack of public awareness regarding nutritional aspects, economic factors, exclusive breastfeeding, complementary feeding, and genetic factors of parents in Neglasari Village. It is hoped that implementing this service activity will be an effort to reduce stunting rates in Indonesia. Abstrak Stunting merupakan masalah kurang gizi yang disebabkan oleh pemberian makanan yang tidak sesuai dengan kebutuhan gizi. Hal ini juga mencerminkan pertumbuhan terhambat akibat gizi buruk dan kesehatan yang kurang baik pada periode sebelum dan sesudah kelahiran. Berdasarkan pengabdian di Desa Neglasari, teridentifikasi permasalahan utama yakni kurangnya pemahaman masyarakat tentang stunting serta kekurangan informasi terkait. Meskipun angka stunting di Desa Neglasari terbilang rendah, penting untuk menciptakan kesadaran dan upaya pencegahan. Oleh karena itu, tujuan pengabdian ini adalah memberikan edukasi kepada masyarakat Desa Neglasari, Kecamatan Salawu, Kabupaten Tasikmalaya, terkait stunting. Metode yang diterapkan dalam pengabdian ini adalah penyuluhan selama satu bulan di setiap Posyandu di Desa Neglasari. Kelompok KKN Desa Neglasari memberikan edukasi bekerja sama dengan perangkat desa dan puskesmas untuk pelaksanaan penyuluhan berkaitan dengan stunting di Desa Neglasari. Berdasarkan hasil pelaksanaan pengabdian dapat diambil simpulan bahwa masih kurangnya kesadaran masyarakat mengenai aspek gizi, faktor ekonomi, pemberian ASI eksklusif, pemberian MPASI, dan faktor genetik dari orang tua di Desa Neglasari. Pelaksanaan kegiatan pengabdian ini diharapkan menjadi salah satu upaya untuk menurunkan angka stunting di Indonesia. Kata Kunci: Anak; edukasi masyarakat; stunting